1999
DOI: 10.1359/jbmr.1999.14.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Effects of Strength Training on Bone Structure and Geometry of Ultradistal Radius in Postmenopausal Women

Abstract: Knowledge of the effects of exercise on bone mass in postmenopausal women is limited and controversial. Animal studies have shown that the response of bone to bending strain is an alteration of bone geometry. We studied 250 postmenopausal women, aged 52-72 years, willing to participate in a 6-month exercise program. The first 125 started the program immediately and the remaining 125 served as controls. The training program included exercises designed to maximize the stress on the wrist. One hundred and eightee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
129
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 26 publications
11
129
2
Order By: Relevance
“…Parallel results have also been observed in some intervention studies on premenopausal [31] and postmenopausal [28,32,33] women after six to twelve months' strength and/or impact training. Interventions targeting bone structure among older people are, however, scarce and comparison of the results is challenging due to variation in study populations, training programs, intervention duration and the bone sites measured.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Parallel results have also been observed in some intervention studies on premenopausal [31] and postmenopausal [28,32,33] women after six to twelve months' strength and/or impact training. Interventions targeting bone structure among older people are, however, scarce and comparison of the results is challenging due to variation in study populations, training programs, intervention duration and the bone sites measured.…”
Section: Discussionsupporting
confidence: 76%
“…The adaptation in this exercise training program, as in some previous studies [28][29][30], occurred in bone structure and, theoretically, in bending strength without increases in BMD.…”
Section: Discussionmentioning
confidence: 59%
“…For example, Kerr et al [52] found in postmenopausal women that BMD at the ultradistal radial site was increased following a 1-year strength training program. A 6-month strengthening program designed to maximize the stress on the wrist also increased the cortical BMC at ultradistal radius in postmenopausal women [53].…”
Section: Discussionmentioning
confidence: 92%
“…A redistribution of the mineral of a bone without changes in the total amount of bone mineral or bone's outer geometry, has also been shown to be possible. 1,8 Earlier studies of tennis players 10,22,31 suggested that the outer dimensions of the playing-arm bones are larger than those of their nonactive counterparts. In addition, in the CT study by Dalen et al, 10 the marrow cavity area of the humeral shaft of seven professional tennis players was examined.…”
Section: Discussionmentioning
confidence: 99%